Qifuyin alleviates anxiety and depression in 3×Tg-AD mice by modulating neuroendocrine function - Yu, Tianhao; Yu, Ying; Zhao, Junqi; Li, He; Lu, Hui; Li, Yangyi; Peng, Yuqi; Wang, Shixue; Wei, Wendi; Cheng, Xiaorui (Frontiers in Psychiatry, 2025)
BackgroundAlzheimer’s disease (AD) is frequently accompanied by behavioral and psychological symptoms of dementia (BPSD). Studies have shown that 3×Tg-AD mice, a classical animal model of AD, exhibit anxiety and depression-like behaviors characteristic of BPSD.ObjectiveThis study investigated the effects of Qifuyin on anxiety and depression-like behaviors in 3×Tg-AD mice.MethodsThe 20 male and female C57BL/6 mice at 10.3 months of age were used as the control group, while the 82 male and female 3×Tg-AD mice of the same age were divided into five groups. The control and model groups were gavaged with solvent, the positive medicine group received a combination of donepezil and memantine, and the Qifuyin (QFY) groups were divided into three doses: low, medium, and high. The effects of QFY on anxiety-like behaviors in mice were assessed using the open field test (OFT) and elevated plus maze (EPM) test, while depression-like behaviors were evaluated through the forced swim test (FST) and sucrose splash test (ST). Plasma levels of corticosterone (CORT), testosterone (T), and estradiol (E2) were measured using ELISA, while adrenocorticotropic hormone (ACTH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), corticotropin-releasing hormone (CRH), and gonadotropin-releasing hormone (GnRH) were quantified via radioimmunoassay. Differences in plasma hormone levels among groups were analyzed using principal component analysis (PCA). Pearson correlation analysis was conducted to explore the relationships between plasma hormones and behavioral phenotypes, and multiple linear regression was employed to identify the hormones most strongly correlated with anxiety and depression-like behaviors in mice following QFY treatment.ResultsIn 3×Tg-AD mice, anxiety-like behaviors were characterized by reduced the duration, number of visits, and total distances in central area during the OFT. The EPM revealed reduced the duration and frequency in the open arms for both sexes. Depression-like behaviors were evident in the FST, with increased immobility, and in the ST, with prolonged grooming latency in both sexes and reduced grooming frequency in females. The treatment of QFY alleviated these behaviors. In males, In the model group, plasma ACTH, GnRH, and FSH levels were significantly decreased. In the QFY-treated group, plasma CRH levels were significantly reduced, while GnRH levels were significantly increased. In the model group of females, plasma ACTH levels were significantly elevated, while FSH and LH levels were markedly reduced. In the QFY-treated group, plasma CORT levels were significantly decreased, whereas FSH and LH levels were significantly increased. Multiple linear regression indicated QFY mainly mitigates anxiety and depression-like symptoms through modulating GnRH in males and T and ACTH in females.ConclusionsThe administration of QFY alleviates anxiety and depression in 3×Tg-AD mice by regulating the HPA, HPT and HPO axes.